Factors Associated With Quality Of Life People Living With Hiv/Aids At Yayasan Peduli Kelompok Dukungan Teman Sebaya (YPKDS) In Makassar City - Framita Rahman; Bahtiar Bahtiar; Andi Fajrin Permana; Muhammad Adhan Kurniawan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
In the current era of HAART, PLWHA can live longer, but that does not mean they lived a satisfying and quality life. This makes PLWHA vulnerable to various health problems.Thus, the aim of this study is to see factors that may associate with the quality of life people with HIV/AIDS. This research was using a cross sectional study. The selected location was YPKDS Makassar with total sample 67 respondents. The sociodemographic analyses found that mostly respondents were male. Most of the respondent were Islam (89,6%), single (58,2%), and living together with their closest family members (62.7%). The respondents mostly have a job and most of them already under medication for less than or in 2 years. Gender, period on medication and stigma were associate with quality of life people with HIV/AIDS. The conclusion was there were several factors that associate with quality of life and need to be analyzed further.